2021
DOI: 10.3390/en14154684
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Microbes in the Petroleum Field: Analyzing the Credibility of Microbial Enhanced Oil Recovery (MEOR)

Abstract: Crude oil is a major energy source that is exploited globally to achieve economic growth. To meet the growing demands for oil, in an environment of stringent environmental regulations and economic and technical pressure, industries have been required to develop novel oil salvaging techniques. The remaining ~70% of the world’s conventional oil (one-third of the available total petroleum) is trapped in depleted and marginal reservoirs, and could thus be potentially recovered and used. The only means of extractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 171 publications
(235 reference statements)
0
9
0
Order By: Relevance
“…These bacteria are collectively known to produce CO 2 and H 2 gases as well as acetic, lactic, butyric, and propionic acids that have roles in MEOR. 17,25,41 The increasing pressure and drop in pH imply that the production of some or all of these was stimulated by nutrient supplementation. However, production of H 2 S by Campylobacteria, such as Sulfurospirillium and Malaciobacter, 43,47 may have also been stimulated.…”
Section: In Vitro Screening Identifies Candidate Wells and Nutrient P...mentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteria are collectively known to produce CO 2 and H 2 gases as well as acetic, lactic, butyric, and propionic acids that have roles in MEOR. 17,25,41 The increasing pressure and drop in pH imply that the production of some or all of these was stimulated by nutrient supplementation. However, production of H 2 S by Campylobacteria, such as Sulfurospirillium and Malaciobacter, 43,47 may have also been stimulated.…”
Section: In Vitro Screening Identifies Candidate Wells and Nutrient P...mentioning
confidence: 99%
“…[42][43][44][45] These populations were distinct from others in the literature, 13,37 a finding that is not unexpected given that each community is driven by un environmental conditions such as temperature, salinity, pH, nutrient availability, and oil gravity among other factors. 25 However, there is no known correlation between native microbial community and MEOR success. Therefore, we pursued in vitro functional screening to evaluate candidate wells for MEOR microbiome engineering with top-down designs.…”
Section: Wells Within the Same Basin Have Unique Properties And Micro...mentioning
confidence: 99%
See 1 more Smart Citation
“…[29] The demand for bioproducts used during advanced oil recovery operations is expected to grow significantly with oil wells aging. [30][31][32][33][34] Thus, the global market of xanthan was estimated at $897 million and is projected to reach $1.5 billion by 2026, [35] due to the growing demand for gluten-free food and beverage additives as well as byproducts for enhanced oil recovery operations.…”
Section: Introductionmentioning
confidence: 99%
“…Under petroleum reservoir anaerobic environments, the coexistence and/or competition of different functional microorganisms could directly affect the quality of petroleum and the efficiency of petroleum recovery. In particular, the current microbial enhanced oil recovery (MEOR) technology is widely used to extract residual petroleum from low-productivity reservoirs by converting hydrocarbons through microbial fermentation and methanogenesis ( Meslé et al, 2013 ; Quraishi et al, 2021 ). Previous studies have found that petroleum hydrocarbons can be degraded by a variety of microorganisms following a quasi-step-by-step biodegradation process ( Meslé et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%